Public debt and the threat of secession - Molato-Gayares, Rhea M. (2019)
This paper establishes a model of public debt as a strategic instrument in preventing secession. Using a dynamic game with perfect information, it shows that debt can be used to pre-empt a country’s separation if the seceding region’s potential gain from independence is strictly decreasing in debt. If so, the national government can prevent this region from leaving the union by setting higher levels of debt so that it reaches a certain threshold level. When the debt level is sufficiently high, this region will find it more beneficial to stay with the union rather than to become an independent state. This paper also finds that the majority region may use debt as a strategic instrument to preserve the union if it is better off in a country with debt than as a separate state with savings.
Keywords: Public debts; Secession; Federations